Analysis of the Implementation of Full Day Calistung in Improving Ability (Reading, Writing, and Arithmetic) in Grade 1 Children at SDIT An-Nahl, Guguak District - Natasya, Putri; Trisnawati, Yane; Febrianti, Nabila; Marwan, Syaiful (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The article writer uses a type of participatory action research method. This is because the PAR method is an action considered as